2022
DOI: 10.18400/tekderg.677447
|View full text |Cite
|
Sign up to set email alerts
|

Lightweight Cement-Based Composites Incorporating Hollow Glass Microspheres: Fresh and Hardened State Properties

Abstract: This research aims to develop a lightweight cementitious composite with satisfying mechanical and good thermal insulating properties. Two different types of hollow glass microspheres (HGM) were used as lightweight aggregates and were substituted with fine aggregate by 10, 20, and 40% by volume. The rheological, physical, mechanical, and microstructural properties of the resulting HGM-incorporated composites were investigated and correlations were established between physical and mechanical test results. The re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 60 publications
1
1
0
Order By: Relevance
“…8 and Table 6). Similar trends were also observed by other studies especially at lower substitution ratio of HGM [91][92][93]. Although the incorporation of HGM increased the amount of voids in the matrix, several benefits were also triggered by the HGM inclusion: The use of a small amount of HGM could reduce the entrapped air content of the paste matrix owing to the lubrication effect [91].…”
Section: Synergistic Effects Of Uhpc and Hgmsupporting
confidence: 85%
“…8 and Table 6). Similar trends were also observed by other studies especially at lower substitution ratio of HGM [91][92][93]. Although the incorporation of HGM increased the amount of voids in the matrix, several benefits were also triggered by the HGM inclusion: The use of a small amount of HGM could reduce the entrapped air content of the paste matrix owing to the lubrication effect [91].…”
Section: Synergistic Effects Of Uhpc and Hgmsupporting
confidence: 85%
“…This result means that, within a specific amount of HGM usage, the amount of HGM had insignificant effect on the strength of the L-UHPC. Previous studies [101][102][103] also reported that the use of HGM below a specified volume could slightly increase the mechanical properties of the concrete mixtures.…”
Section: Roles Of Hgm and Lwa In L-uhpcmentioning
confidence: 88%